2013
DOI: 10.1158/0008-5472.can-12-2202
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Function as Novel Osteoclast Progenitors Enhancing Bone Loss in Breast Cancer

Abstract: Enhanced bone destruction is a hallmark of various carcinomas such as breast cancer, where osteolytic bone metastasis is associated with increased morbidity and mortality. Immune cells contribute to osteolysis in cancer growth but the factors contributing to aggressive bone destruction are not well understood. In this study, we demonstrate the importance of myeloid-derived suppressor cells (MDSC) in this process at bone metastatic sites. Since MDSC originate from the same myeloid lineage as macrophages, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 46 publications
(55 reference statements)
5
130
0
Order By: Relevance
“…In addition, OCPs shared the phenotype with the myeloid-derived suppressor cell (MDSC) population and exerted an immunomodulatory function upon a co-adoptive transfer with SKG CD4 + T lymphocytes. Sawant et al also observed that bone marrow CD11b + Gr-1 + CD80 lo CD115 + F4/80 -MDSCs of breast tumor-bearing mice, found among the immature myeloid population, can be differentiated into functional osteoclasts [34].…”
Section: Murine Osteoclast Progenitorsmentioning
confidence: 96%
“…In addition, OCPs shared the phenotype with the myeloid-derived suppressor cell (MDSC) population and exerted an immunomodulatory function upon a co-adoptive transfer with SKG CD4 + T lymphocytes. Sawant et al also observed that bone marrow CD11b + Gr-1 + CD80 lo CD115 + F4/80 -MDSCs of breast tumor-bearing mice, found among the immature myeloid population, can be differentiated into functional osteoclasts [34].…”
Section: Murine Osteoclast Progenitorsmentioning
confidence: 96%
“…MDSCs (CD11b þ Gr-1 þ ) obtained from the bone marrow of mice with murine breast cancer cell line 4T1 bone metastases (MDSCs þ bone mets ) differentiate into TRAP-positive, bone resorptive osteoclasts in vitro and express CTSK, carbonic anhydrase-2, MMP-9 and NO. 56 However, MDSCs from the bone marrow of mice without bone metastases, regardless of other metastatic sites (lung, lymph node, spleen or blood), do not differentiate into osteoclasts, suggesting that the osteoclast differentiation of MDSCs is unique to the bone metastatic environment. 56 In addition, when MDSCs þ bone mets are transplanted, osteoclast differentiation of MDSCs þ bone mets and bone distraction are observed in recipient mice.…”
Section: Macrophagesmentioning
confidence: 99%
“…56 However, MDSCs from the bone marrow of mice without bone metastases, regardless of other metastatic sites (lung, lymph node, spleen or blood), do not differentiate into osteoclasts, suggesting that the osteoclast differentiation of MDSCs is unique to the bone metastatic environment. 56 In addition, when MDSCs þ bone mets are transplanted, osteoclast differentiation of MDSCs þ bone mets and bone distraction are observed in recipient mice. 56 Interestingly, both in vitro and in vivo osteoclastogenesis mediated by MDSCs þ bone mets are inhibited by blocking NO.…”
Section: Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations